Firm Characteristics and Corporate Cash Holdings: A Managerial Perspective from Kenyan Private Manufacturing Firms - Kariuki, Samuel N.; Namusonge, Gregory S.; Orwa, George O. (GreenField Advanced Research Publishing House, 2015)
The purpose of this study was to investigate the managerial perspectives on the firm characteristics and corporate cash holdings among in private manufacturing firms in Kenya. Several international studies show that companies retain important cash holdings. Yet, the prevalent questions have been: Why do firms hold huge amount of cash? Is there an optimum level of cash holdings? A review of the extant literature reveals that mostly the current studies depend on secondary data to provide evidence on corporate cash holdings. This survey-based study sought to bridge this gap in the literature by examining chief finance officers of private manufacturing firms to comprehensively investigate the corporate cash holdings from a managerial perspective. A sample of 156 firms was selected for the survey using stratified random sampling technique from which 117 questionnaires were returned. The primary data was sourced through personally administered survey questionnaires to the chief finance officers. Data was analyzed using descriptive statistics and inferential statistics (independent sample t-test). The study concludes that CFOs of private manufacturing firms in Kenya are of the view that growth opportunities, leverage and debt structure, firm size, likelihood of financial distress and cash flow variability are all important drivers of corporate cash holding policy.
Keywords: Cash holdings; growth opportunities; leverage; firm size; financial distress; cash flow variability